2018
DOI: 10.4103/ijccm.ijccm_462_17
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in acute kidney injury patients admitted to medicine intensive care unit in a Rural Tertiary Care Hospital

Abstract: Background:Acute kidney injury (AKI) is a challenging problem faced by intensive care clinicians worldwide, and it is associated with high morbidity and mortality, especially in critically ill patients.Materials and Methods:A hospital-based prospective, observational study was conducted in patients of AKI admitted to the Intensive Care Unit (ICU) of the Department of Medicine in a rural tertiary care hospital located in central India. Data of all consecutive AKI inpatients related to demographic variables, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
4
22
0
2
Order By: Relevance
“…Notably, our study determined that the mortality rates of sepsis and acute renal failure were identical. A study that analysed this occurrence demonstrated that sepsis was the most common cause of acute renal failure (19). In our study, in the geriatric group aged over 85 years, the mortality rate was higher than 85% in patients with high fever and acute renal failure, probably secondary to sepsis.…”
Section: Discussionsupporting
confidence: 39%
“…Notably, our study determined that the mortality rates of sepsis and acute renal failure were identical. A study that analysed this occurrence demonstrated that sepsis was the most common cause of acute renal failure (19). In our study, in the geriatric group aged over 85 years, the mortality rate was higher than 85% in patients with high fever and acute renal failure, probably secondary to sepsis.…”
Section: Discussionsupporting
confidence: 39%
“…Acute kidney injury (AKI) is common in the intensive care unit (ICU), and there is evidence that even a small increase in serum creatinine may be associated with increased risk of mortality [13]. AKI can be defined by either an elevation in serum creatinine or a reduced urine output according to the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines [4].…”
Section: Introductionmentioning
confidence: 99%
“…Estudos recentes mostram que o APACHE II é considerado um adequado índice preditivo de complicações neurológicas em pacientes cardíacos comatosos após parada cardiorrespiratória 27 e uma excelente ferramenta prognóstica para mortalidade em pacientes com lesão renal aguda. 28 Entretanto, essas pesquisas, apesar de analisarem complicações neurológicas e renais ocorridas em UTI, não abordaram especificamente pacientes submetidos à CRM isolada.…”
Section: Discussionunclassified